Investigating Ultrafiltration Membranes and Operation Modes for Improved Lentiviral Vector Processing - Jennifer J. Labisch; Maria Evangelopoulou; Tobias Schleuß; Andreas Pickl (Engineering in Life Sciences)
ABSTRACT The demand for lentiviral vectors (LVs) as tools for ex vivo gene therapies is ever‐increasing. Despite their promising applications, challenges in LV production remain largely due to the fragile envelope, which challenges the maintenance of vector stability. Thus, downstream processing optimization to enhance efficiency, yield, and product quality is necessary. This study investigated the influence of membrane types and filtration devices during ultrafiltration (UF). Nine different membrane materials consisting of polyethersulfone (PES), regenerated cellulose, or Hydrosart, with distinct molecular weight cutoffs, were evaluated in stirred cells, centrifugal ultrafilters, and crossflow cassettes. The evaluation was based on the ability to retain infectious LV particles and remove impurities. The analysis revealed that a reinforced 100 kDa PES and a 300 kDa Hydrosart membrane had the best overall ability to concentrate infectious LVs and remove DNA, especially when operated in a stirred cell. Challenges were seen in the nonoptimized crossflow cassette process, where infectious LV recovery was generally lower compared to other devices. We demonstrated that membrane material and filtration device have a direct impact on the efficiency of LV UF.